1988
DOI: 10.1111/j.1651-2227.1988.tb10590.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Morbidity, Growth and Development of Babies Weighing 501–1000 Grams and 1001–1500 Grams at Birth

Abstract: During the five-year period, January 1980 to December 1984, 149 babies of extremely low birthweight (ELBW; 501-1,000 g) and 296 of very low birthweight (VLBW; 1,001-1,500 g) were admitted to King's College Hospital, Neonatal Intensive Care Unit. The survival rates were 51.7% and 82.8% respectively. There were more peri- and postnatal problems in the ELBW babies than the VLBW babies and these differences were highly significant. All surviving babies born between January 1980 and December 1982 were followed up u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…We included a greater number of infants born at less than 24 weeks of gestation, in whom mortality is higher, than the previous study [6] and this is likely to have influenced our results. Our infants were all ventilated and thus likely to be sicker than those included in earlier studies which reported mortality rates of (55% in 1976-1980 [12]; 48% in 1980-1984 [2]; and 44% in 1981-1985 [12]. These data suggest that survival rates of even very immature infants are continuing to increase slowly with time.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…We included a greater number of infants born at less than 24 weeks of gestation, in whom mortality is higher, than the previous study [6] and this is likely to have influenced our results. Our infants were all ventilated and thus likely to be sicker than those included in earlier studies which reported mortality rates of (55% in 1976-1980 [12]; 48% in 1980-1984 [2]; and 44% in 1981-1985 [12]. These data suggest that survival rates of even very immature infants are continuing to increase slowly with time.…”
Section: Discussionmentioning
confidence: 47%
“…It is difficult to compare this figure to those reported from different series which have included different study populations. When related to birth weight, the reported incidence of CLD varies from 5% [2] to 75% [19]. Our infants were all very immature and ventilated and thus the highest risk group, we therefore feel our incidence is encouragingly low.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…5,6 While in a study conducted by Mehta B. et al 7 found overall mortality was 17% and in a study by Singh Uma et al 1 overall mortality was 12.7% . Common causes of mortality were RDS (85.4 %), Sepsis (10.4 %) and Aspiration pneumonia (4.1 %).…”
Section: Diseasesmentioning
confidence: 95%
“…Cases were limited to term (≥ 38 weeks), singleton deliveries, with no known intrauterine growth retardation (birthweights ≤ 3rd centile on charts standardized for length of gestation, sex, ordinal position, maternal height, and mid-pregnancy weight [Tanner and Thompson 1970]). Preterm and low-birthweight babies were excluded because of the known association with below average postnatal growth (Brothwood et al 1987). Cases of faltering growth were defined as having a weight for age ≤ 3rd centile, with this growth trajectory having been sustained for at least 3 months or more (Tanner and Whitehouse 1984).…”
Section: Subjectsmentioning
confidence: 99%